2024
DOI: 10.1038/s41598-023-51099-9
|View full text |Cite
|
Sign up to set email alerts
|

The amount of antioxidants in honey has a strong relationship with the plants selected by honey bees

Zahra Shakoori,
Elham Salaseh,
Ahmad Reza Mehrabian
et al.

Abstract: As one of the main sources of natural antioxidants, flowering plants play a role in the prevention and treatment of many diseases directly and indirectly. Honey is considered as an important nutrient in the supply of natural antioxidants, the amount of which is directly dependent on the plant origin and geographical location of the bee feeding place. The existence of valuable communities of native and endemic plant species has turned Alborz, Zagros and Azerbaijan into the most important hubs of honey productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
(67 reference statements)
1
0
0
Order By: Relevance
“…Interestingly, the antioxidant capacity of all these poly-floral honeys was comparable with that of mono-floral Manuka 5+ honey (DPPH RSA of 43.48%), suggesting that they could be used as natural antioxidant agents to protect human cells against the harmful effects of free radicals [ 25 ]. The above DPPH RSA values were within the range reported in previous studies (31.1–86.9%) [ [26] , [27] , [28] , [29] , [30] ]. However, the Chogoria honey from the Eastern region of Kenya was the least potent in terms of antioxidant activity, with a DPPH RSA of 8.45%.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, the antioxidant capacity of all these poly-floral honeys was comparable with that of mono-floral Manuka 5+ honey (DPPH RSA of 43.48%), suggesting that they could be used as natural antioxidant agents to protect human cells against the harmful effects of free radicals [ 25 ]. The above DPPH RSA values were within the range reported in previous studies (31.1–86.9%) [ [26] , [27] , [28] , [29] , [30] ]. However, the Chogoria honey from the Eastern region of Kenya was the least potent in terms of antioxidant activity, with a DPPH RSA of 8.45%.…”
Section: Resultssupporting
confidence: 90%
“…However, the total polyphenol content present in our samples was lower than that observed by Otmani et al [44], who found a quantity of total polyphenols of no less than 64 mg GAE/100 g of product in different types of Fabaceae honey from the Algerian territory. However, total polyphenols and other biochemical characteristics of honey are related to the territory [44], the type of plant selected by the bees [45], and the period of pollen collection by bees [46]. 2 show the polyphenols' profile of the five legume honeys, determined through UPLC analysis.…”
Section: Total Polyphenols and Polyphenol Profilementioning
confidence: 99%
“…Some authors reported that the total phenolic content in honey cannot be positively correlated with its antioxidant activity at any time (Al-Mamary et al, 2002;Küçük et al, 2007). Research shows that the flower source determines honey quality (Castiglioni et al, 2017;Boussaid et al, 2018;Shakoori et al, 2024), along with elevation (Neupane et al, 2015), climate (Liang et al, 2018;Liu et al, 2022), color value (Beretta et al, 2005), vitamins and amino acids (Liu et al, 2023), and other parameters (Gül and Pehlivan, 2018). Another study suggested that the bee hive's geographical locations and plant resources directly and significantly correlate with honey quality (Gül and Pehlivan, 2018;Shakoori et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that the flower source determines honey quality (Castiglioni et al, 2017;Boussaid et al, 2018;Shakoori et al, 2024), along with elevation (Neupane et al, 2015), climate (Liang et al, 2018;Liu et al, 2022), color value (Beretta et al, 2005), vitamins and amino acids (Liu et al, 2023), and other parameters (Gül and Pehlivan, 2018). Another study suggested that the bee hive's geographical locations and plant resources directly and significantly correlate with honey quality (Gül and Pehlivan, 2018;Shakoori et al, 2024). This close relationship is reflected in the fact that, on the one hand, the effective substances in plants follow the collecting bees into the beehive and ferment into honey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation